2014
DOI: 10.1371/journal.pone.0104313
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BPSS1521 (bprD), a Regulator of Burkholderia pseudomallei Virulence Gene Expression in the Mouse Model

Abstract: The Gram-negative saprophytic bacterium Burkholderia pseudomallei is the causative agent of melioidosis, a severe infectious disease of both humans and animals. Severity of the disease is thought to be dependent on both the health status of the host, including diabetes mellitus and kidney disease, and bacterial-derived factors. To identify the bacterial factors important during an acute infection, gene expression profiles in the spleen, lung, and liver of BALB/c (Th2 prototype) and C57BL/6 mice (Th1 prototype)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In a previous study, when bprD was deleted along with bprB and bprC , there was no change in levels of transcription of other Bsa T3SS genes leaving the role of BprD as a regulator in doubt ( 48 ). More recently, a bprD mutant of B. pseudomallei K96243 was shown to have increased expression of bprC ( 80 ), a downstream gene in the same operon shown to be involved in regulation of the virulence-associated T6SS ( 81 ). The bprD mutant also showed decreased time to death in intraperitoneally inoculated BALB/c mice demonstrating its importance in vivo and indicating its possible role as a negative regulator of virulence ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, when bprD was deleted along with bprB and bprC , there was no change in levels of transcription of other Bsa T3SS genes leaving the role of BprD as a regulator in doubt ( 48 ). More recently, a bprD mutant of B. pseudomallei K96243 was shown to have increased expression of bprC ( 80 ), a downstream gene in the same operon shown to be involved in regulation of the virulence-associated T6SS ( 81 ). The bprD mutant also showed decreased time to death in intraperitoneally inoculated BALB/c mice demonstrating its importance in vivo and indicating its possible role as a negative regulator of virulence ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a bprD mutant of B. pseudomallei K96243 was shown to have increased expression of bprC ( 80 ), a downstream gene in the same operon shown to be involved in regulation of the virulence-associated T6SS ( 81 ). The bprD mutant also showed decreased time to death in intraperitoneally inoculated BALB/c mice demonstrating its importance in vivo and indicating its possible role as a negative regulator of virulence ( 80 ). It is not without precedent that a regulator of the T3SS is also a substrate for secretion ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…MNGCs, referred to as a “hallmark” of B . pseudomallei infection [ 55 ], have been reported in other studies of chronic melioidosis in mice [ 33 , 55 ], Madagascar hissing cockroaches [ 56 ], and in human autopsies [ 57 ]. Surprisingly, there are few descriptions of MNGCs in mice infected with B .…”
Section: Introductionmentioning
confidence: 91%
“…Surprisingly, there are few descriptions of MNGCs in mice infected with B . pseudomallei [ 33 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…While this sex bias observed in melioidosis may be primarily associated with health and/or occupational risk factors (e.g., alcoholism or occupational exposure through rice cultivation), it is important to examine both sexes of mice in order to get the most complete dataset possible [40]. There have been several reports using male mice as melioidosis models [41][42][43][44][45][46][47][48][49][50][51], but only a few have actually either compared males and females or characterized the disease pathology within male mice [41,[52][53][54]. Emery et al reported evidence demonstrating that female mice in their experiments tended to be more resistant to infection caused by intranasal instillation of B. pseudomallei [53].…”
Section: Introductionmentioning
confidence: 99%